Performance of masonry wall joint corner with perforated plate in non engineering building - Roro P. Hapsari; Hidajat Sugihardjo; Ahmad B. Habieb (Institut Teknologi Sepuluh Nopember (ITS), 2023)
Indonesian houses are characterized as non-engineered and vernacular, constructed using local material, techniques, and architectural style. As a results, these houses are typically built without the involvement of experts. In Indonesia, most lower-class houses are unreinforced masonry (URM), masonry without moment resisting frame. The absence of those frame makes URM highly vulnerable to earthquakes and makes the masonry walls the main load bearers. This study analyses the performance of corner joint masonry walls with perforated plates to enhance the integrity between the perpendicular walls. This research was carried out experimentally. The results indicate that URM joint corner walls without perforated plates has the highest load capacity and ductility. Perforated plates in layers of masonry walls can decrease the lateral load capacity by 55%. The failure pattern that occurred are slip failure, with cracks appearing at the mortar-brick joint and mortar-perforated plate interfaces. From the tests that have been carried out, it was found that perforated plate could reduce the cohesiveness of the walls rather than enhance the integrity of the perpendicular walls.